"That is Giving a Banquet": Neighbor‐Love as Spiritualization of Romantic Loves in Works of Love. Issue 2 (23rd July 2022) - Hanson, Jeffrey
ABSTRACT: Recent readings of Kierkegaard's Works of Love have admirably shown how his apparent reservations about romantic love can be deflected on his own terms by imbuing them with some of the moral rigor of neighbor‐love. This paper argues however that these readings must be complemented by the reverse argument, which would show how some of the qualities of romantic loves are in fact preserved in neighbor‐love. By drawing on his dialectics of sensate love, psychical love, spiritual love, and self‐love, I show how Kierkegaard believes neighbor‐love should be impartial and yet exhibit some of the character of preferential romantic loves.